ChemInform Abstract: Conjugate‐Base‐Stabilized Broensted Acids: Catalytic Enantioselective Pictet—Spengler Reactions with Unmodified Tryptamine. Issue 29 (22nd July 2014) - Mittal, Nisha; Sun, Diana X.; Seidel, Daniel
Abstract Benzaldehydes bearing electron‐withdrawing substituents in the para position afford the corresponding tetrahydro‐β‐carbolines in high yields and enantioselectivities.